Validation of a portable monitor compared with polysomnography for screening of obstructive sleep apnea in polio survivors - Ding, Qidi; Liu, Jianghua; Wu, Jinxian; Du, Juan; Li, Xiao; Wang, Meng; Sun, Yunliang; Yu, Yan; Wang, Jingyu; Sun, Ting; Zhang, Chi; Lv, Changjun; et al. (Frontiers in Neurology, 2023)
Subjective Sleep-disordered breathing (SDB) is highly prevalent in polio survivors. Obstructive sleep apnea (OSA) is the most frequent type. Full polysomnography (PSG) is recommended for OSA diagnosis in patients with comorbidities by current practice guidelines, but it is not always accessible. The purpose of this study was to evaluate whether type 3 portable monitor (PM) or type 4 PM might be a viable alternative to PSG for the diagnosis of OSA in postpolio subjects. Methods A total of 48 community-living polio survivors (39 men and 9 women) with an average age of 54.4 ± 5.3 years referred for the evaluation of OSA and who volunteered to participate were recruited. First, they completed the Epworth Sleepiness Scale (ESS) questionnaire and underwent pulmonary function testing and blood gas tests the day before PSG night. Then, they underwent an overnight in-laboratory PSG with a type 3 PM and type 4 PM recording simultaneously. Results The AHI from PSG, respiratory event index (REI) from type 3 PM, and ODI3 from type 4 PM was 30.27 ± 22.51/h vs. 25.18 ± 19.11/h vs. 18.28 ± 15.13/h, respectively (P < 0.001). For AHI ≥ 5/h, the sensitivity and specificity of REI were 95.45 and 50%, respectively. For AHI ≥ 15/h, the sensitivity and specificity of REI were 87.88% and 93.33%, respectively. The Bland–Altman analysis of REI on PM vs. AHI on PSG showed a mean difference of −5.09 (95% confidence interval [CI]: −7.10, −3.08; P < 0.001) with limits of agreement ranging from −18.67 to 8.49 events/h. ROC curve analysis for patients with REI ≥ 15/h showed an area under the curve (AUC) of 0.97. For AHI ≥ 5/h, the sensitivity and specificity of ODI3 from type 4 PM were 86.36 and 75%, respectively. For patients with AHI ≥ 15/h, the sensitivity was 66.67%, and the specificity was 100%. Conclusion Type 3 PM and Type 4 PM could be alternative ways to screen OSA for polio survivors, especially for moderate to severe OSA.